Temporal representation impairment in developmental dyslexia for unisensory and multisensory stimuli. Issue 5 (14th June 2020) - Gori, Monica; Ober, Kinga M.; Tinelli, Francesca; Coubard, Olivier A.
Abstract: Dyslexia has been associated with a problem in visual–audio integration mechanisms. Here, we investigate for the first time the contribution of unisensory cues on multisensory audio and visual integration in 32 dyslexic children by modelling results using the Bayesian approach. Non‐linguistic stimuli were used. Children performed a temporal task: they had to report whether the middle of three stimuli was closer in time to the first one or to the last one presented. Children with dyslexia, compared with typical children, exhibited poorer unimodal thresholds, requiring greater temporal distance between items for correct judgements, while multisensory thresholds were well predicted by the Bayesian model. This result suggests that the multisensory deficit in dyslexia is due to impaired audio and visual inputs rather than impaired multisensory processing per se. We also observed that poorer temporal skills correlated with lower reading skills in dyslexic children, suggesting that this temporal capability can be linked to reading abilities. Abstract : Multisensory audio visual processing in dyslexia is due to impaired audio and visual inputs rather than impaired multisensory processing per se.